Determinants of students' entrepreneurial intention - a comparative study in Poland and Hong Kong. (16th June 2020) - Law, Kris M.Y.; Jakubiak, Monika
This study investigates the entrepreneurial intentions in association with innovativeness and attitudes, between two groups of university students from Poland and Hong Kong. The present study was conducted among 1, 000 students from universities in Hong Kong and 552 students from Poland. Four behavioural variables (entrepreneurial intention, attitude toward entrepreneurship, efficacy) were measured. First, attitudes, innovativeness and self-efficacy affect entrepreneurial intention. Second, significant differences between student groups from different cultural backgrounds are found. Thirdly, engineering and science students from Hong Kong manifest stronger entrepreneurial intentions than those from business courses whereas opposite results were obtained concerning Polish students. Fourthly, students from business courses exhibit slightly stronger entrepreneurial intentions than those from engineering and science. Our study shows clearly that the difference between the two countries entrepreneurial intention is not merely affected by cultural background, but also by discipline.